Kontrol Kualitas Batubara Pada Proses Pengangkutan di Site PT BCMP Kabupaten Tanah Bumbu Kalimantan Selatan - Amir, Muh. Karnoha; Shaddad, Aqsal Ramadhan; Dzakir, La Ode (Jurnal of Mining Insight, 2023)
Coal is formed from organic deposits undergoing conversion through the coalification process. Coal is a solid object containing carbon, hydrogen, and oxygen in chemical combination with a small amount of sulfur and nitrogen elements, which are found in the earth's crust derived from plant remains that have undergone metamorphosis over a long period of time. The purpose and objective of this research is to control the process of transporting coal from the stockpile to the coal haulinvessg el and to determine the quality of the coal in the stockpile and coal haulage vessel. The ash value in the stockpile is 3.98% and the coal haulage is 4.13% so that there is an insignificant increase, then the total sulfur in the stockpile is 0.11% and the coal transport vessel 0.10% is a non-significant decrease. then the total moisture in the stockpile obtained a value of 42.15% and coal hauling ships 42.25% an insignificant increase. fixed carbon in the stockpile obtained a value of 31.94% and coal ships 32.11% an insignificant increase. Then the volatile matter in the stockpile obtained a value of 43.21% and coal transport vessels 42.59% an insignificant decrease. And moisture in the stoockpile obtained a value of 20.87% and coal hauling vessels of 21.17% an insignificant increase, then the calori value obtained in the stockpile value of 4.856 and coal hauling vessels of 4.824 there was an insignificant decrease in calories. From the results of the quality of the coal above, it shows that during the process of transporting coal from the stockpile to the coal hauler, the coal quality parameters did not experience a quality drop or significant quality change, so during the coal transportation process there were no factors that affected the quality change significantly.